Original in: IML Berlin, K.-L. 2. Karl Liebknecht and his family in Oberwiesenthal, from left to right: Robert, Sophie, Vera, Karl and Wilhelm Liebknecht - Kaden, ... (1913)
Original in: IML Berlin, K.-L. 2. Karl Liebknecht and his family in Oberwiesenthal, from left to right: Robert, Sophie, Vera, Karl and Wilhelm Liebknecht.